2004
DOI: 10.1107/s010827010401813x
|View full text |Cite
|
Sign up to set email alerts
|

Mg7(AsO4)2(HAsO4)4: a new magnesium arsenate with a very strong hydrogen bond

Abstract: A new compound, heptamagnesium bis(arsenate) tetrakis(hydrogenarsenate), Mg7(AsO4)2(HAsO4)4, was synthesized by a hydrothermal method. The structure is based on a three-dimensional framework of edge- and corner-sharing MgO6, MgO4(OH)2, MgO5, AsO3(OH) and AsO4 polyhedra. Average Mg-O and As-O bond lengths are in the ranges 2.056-2.154 and 1.680-1.688 A, respectively. Each of the two non-equivalent OH groups is bonded to both an Mg and an As atom. One OH group is involved in a very short hydrogen bond [O.O = 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The TAV and TQE indices are 7.84 and 1.002, 17.16 and 1.004, and 39.77 and 1.010, respectively, for the As1, As2, and As3 tetrahedra. All As-O and As-OH bond lengths fall in the ranges observed in other Ca arsenate minerals and compounds (Ferraris & Chiari 1970, Ferraris & Abbona 1972, 1972a, 1972b, Catti & Ferraris 1974, Catti et al 1980, Catti & Ivaldi 1983, Mihajlović et al 2004, Kolitsch & Bartu 2004, Đorđević & Karanović 2008, Lee et al 2009, but with both the shortest (As-O11) and the longest (As-O12H) bonds within the As3 tetrahedra. Ca1 0.67087(6) 0.72601(4) 0.00250(2) 0.00903(8) 0.0088(1) 0.0097(2) 0.0086(2) -0.0011(2) 0.0013(1) 0.0001(1) Ca2 0.00525(6) 0.85202(4) 0.14094(2) 0.00875(8) 0.0084(1) 0.0089(2) 0.0091(2) 0.0012(2) 0.0012(1) 0.0005(1) Ca3 0.88901(6) 0.32115(4) 0.10694(2) 0.01124(8) 0.0120(1) 0.0128(2) 0.0094(2) 0.0024(2) 0.0030(1) 0.0027(1) Ca4 0.43361(6) 0.36411(4) 0.24537(2) 0.01010(8) 0.0096(1) 0.0096(2) 0.0107(2) -0.0003(2) -0.0005(1) 0.0005(1) As1 0.86851(3) 0.54829(2) 0.21401(1) 0.00704(5) 0.0076(1) 0.0061(1) 0.0073(1) 0.0004(1) 0.0005(1) 0.0006(1) As2 0.54070(3) 0.00128(2) 0.09702(1) 0.00733(5) 0.0071(1) 0.0067(1) 0.0083(1) 0.0006(1) 0.0013(1) 0.0006(1) As3 0.23074(3) 0.58486(2) 0.04956(1) 0.00718(5) 0.0070(1) 0.0070(1) 0.0076(1) 0.0001(1) 0.0010(1) 0.0002(1) O1 0.8563(2) 0.7138(1) 0.21273(6) 0.0096(3) 0.0114(5) 0.0065(7) 0.0112(7) 0.0005(6) 0.0025(5) 0.0003(5) O2 0.1321(2) 0.4972(1) 0.20166(7) 0.0140(3) 0.0118(6) 0.0141(7) 0.0171(8) 0.0037(6) 0.0056(5) 0.0057(5) O3 0.6737(2) 0.4811(1) 0.16106(7) 0.0146(3) 0.0180(6) 0.0100(7) 0.0139(8) -0.0008(6) -0.0063(6) 0.0002(5) O4 0.7917(2) 0.4918(1) 0.27804(6) 0.0121(3) 0.0149(6) 0.0117(7) 0.0104(8) 0.0021(6) 0.0044(5) -0.0008(5) O5 0.5444(2) 0.1643(1) 0.08188(6) 0.0103(3) 0.0124(6) 0.0071(7) 0.0113(7) 0.0017(6) 0.0006(5) 0.0006(5) O6 0.2650(2) 0.9502(1) 0.08624(7) 0.0134(3) 0.0079(5) 0.0146(7) 0.0175(8) 0.0041(6) 0.0011(5) -0.0027(5) O7 0.6643(2) 0.9778(1) 0.16747(6) 0.0117(3) 0.0137(6) 0.0121(7) 0.0090(7) 0.0031(6) 0.0001(5) 0.0018(5) O8 0.7147(2) 0.9148(1) 0.05839(6) 0.0120(3) 0.0124(6) 0.0110(7) 0.0130(8) -0.0039(6) 0.0034(5) 0.0024(5) O9 0.6999(2) 0.3858(1) 0.01805(6) 0.0128(3) 0.0113(6) 0.0202(8) 0.0071(7) 0.0024(6) 0.0013(5) 0.0003(5) O10 0.0132 20.6745(1) 0.06959(7) 0.0114(3) 0.0085(5) 0.0122(7) 0.0131(8) -0.0026(6) -0.0003(5) 0.0029(5) O11 0.1964(2) 0.4254(1) 0.06268(7) 0.0111(3) 0.0142(6) 0.0058(8) 0.0140(8) -0.0008(6) 0.0049(5) -0.0012(5) O12H 0.4885(2) 0.6398(1) 0.08884(6) 0.0101(3) 0.0083(5) 0.0114(7) 0.0100(7) 0.0016(6) -0.0018(5) -0.0001(5) OW1 0.0230(2) 0.1537(1) 0.04187(8) 0.0140(3) 0.0117(6) 0.0102(7) 0.0198(9) 0.0015(6) 0.0010(6) 0.0015 ( groups, and purple spheres: H atoms.…”
Section: Crystal Structure and Chemical Formulamentioning
confidence: 67%
See 1 more Smart Citation
“…The TAV and TQE indices are 7.84 and 1.002, 17.16 and 1.004, and 39.77 and 1.010, respectively, for the As1, As2, and As3 tetrahedra. All As-O and As-OH bond lengths fall in the ranges observed in other Ca arsenate minerals and compounds (Ferraris & Chiari 1970, Ferraris & Abbona 1972, 1972a, 1972b, Catti & Ferraris 1974, Catti et al 1980, Catti & Ivaldi 1983, Mihajlović et al 2004, Kolitsch & Bartu 2004, Đorđević & Karanović 2008, Lee et al 2009, but with both the shortest (As-O11) and the longest (As-O12H) bonds within the As3 tetrahedra. Ca1 0.67087(6) 0.72601(4) 0.00250(2) 0.00903(8) 0.0088(1) 0.0097(2) 0.0086(2) -0.0011(2) 0.0013(1) 0.0001(1) Ca2 0.00525(6) 0.85202(4) 0.14094(2) 0.00875(8) 0.0084(1) 0.0089(2) 0.0091(2) 0.0012(2) 0.0012(1) 0.0005(1) Ca3 0.88901(6) 0.32115(4) 0.10694(2) 0.01124(8) 0.0120(1) 0.0128(2) 0.0094(2) 0.0024(2) 0.0030(1) 0.0027(1) Ca4 0.43361(6) 0.36411(4) 0.24537(2) 0.01010(8) 0.0096(1) 0.0096(2) 0.0107(2) -0.0003(2) -0.0005(1) 0.0005(1) As1 0.86851(3) 0.54829(2) 0.21401(1) 0.00704(5) 0.0076(1) 0.0061(1) 0.0073(1) 0.0004(1) 0.0005(1) 0.0006(1) As2 0.54070(3) 0.00128(2) 0.09702(1) 0.00733(5) 0.0071(1) 0.0067(1) 0.0083(1) 0.0006(1) 0.0013(1) 0.0006(1) As3 0.23074(3) 0.58486(2) 0.04956(1) 0.00718(5) 0.0070(1) 0.0070(1) 0.0076(1) 0.0001(1) 0.0010(1) 0.0002(1) O1 0.8563(2) 0.7138(1) 0.21273(6) 0.0096(3) 0.0114(5) 0.0065(7) 0.0112(7) 0.0005(6) 0.0025(5) 0.0003(5) O2 0.1321(2) 0.4972(1) 0.20166(7) 0.0140(3) 0.0118(6) 0.0141(7) 0.0171(8) 0.0037(6) 0.0056(5) 0.0057(5) O3 0.6737(2) 0.4811(1) 0.16106(7) 0.0146(3) 0.0180(6) 0.0100(7) 0.0139(8) -0.0008(6) -0.0063(6) 0.0002(5) O4 0.7917(2) 0.4918(1) 0.27804(6) 0.0121(3) 0.0149(6) 0.0117(7) 0.0104(8) 0.0021(6) 0.0044(5) -0.0008(5) O5 0.5444(2) 0.1643(1) 0.08188(6) 0.0103(3) 0.0124(6) 0.0071(7) 0.0113(7) 0.0017(6) 0.0006(5) 0.0006(5) O6 0.2650(2) 0.9502(1) 0.08624(7) 0.0134(3) 0.0079(5) 0.0146(7) 0.0175(8) 0.0041(6) 0.0011(5) -0.0027(5) O7 0.6643(2) 0.9778(1) 0.16747(6) 0.0117(3) 0.0137(6) 0.0121(7) 0.0090(7) 0.0031(6) 0.0001(5) 0.0018(5) O8 0.7147(2) 0.9148(1) 0.05839(6) 0.0120(3) 0.0124(6) 0.0110(7) 0.0130(8) -0.0039(6) 0.0034(5) 0.0024(5) O9 0.6999(2) 0.3858(1) 0.01805(6) 0.0128(3) 0.0113(6) 0.0202(8) 0.0071(7) 0.0024(6) 0.0013(5) 0.0003(5) O10 0.0132 20.6745(1) 0.06959(7) 0.0114(3) 0.0085(5) 0.0122(7) 0.0131(8) -0.0026(6) -0.0003(5) 0.0029(5) O11 0.1964(2) 0.4254(1) 0.06268(7) 0.0111(3) 0.0142(6) 0.0058(8) 0.0140(8) -0.0008(6) 0.0049(5) -0.0012(5) O12H 0.4885(2) 0.6398(1) 0.08884(6) 0.0101(3) 0.0083(5) 0.0114(7) 0.0100(7) 0.0016(6) -0.0018(5) -0.0001(5) OW1 0.0230(2) 0.1537(1) 0.04187(8) 0.0140(3) 0.0117(6) 0.0102(7) 0.0198(9) 0.0015(6) 0.0010(6) 0.0015 ( groups, and purple spheres: H atoms.…”
Section: Crystal Structure and Chemical Formulamentioning
confidence: 67%
“…Remarkably, the distance between O12H-H...O3 in vladimirite is only 2.47 Å, which is the shortest donor-acceptor distance (d D-A ) of all Ca arsenate minerals (Ferraris & Ivaldi 1984) and belongs to the shortest known examples, in which the donor and acceptor atoms are symmetrically distinct (Mihajlović & Effenberger 2006, Đorđević & Karanović 2008. Nonetheless, such a short d D-A value has been observed in several synthetic compounds containing the AsO 3 OH groups, such as Sr 5 (As 2 O 7 ) 2 (AsO 3 OH) with d D-A = 2.49 Å (Mihajlović et al 2004), Mg 7 (AsO 4 ) 2 (AsO 3 OH) 4 with d D-A = 2.47 Å (Kolitsch & Bartu 2004), Sr 4 Cu 3 (AsO 4 ) 2 (AsO 3 OH) 4 •3H 2 O with d D-A = 2.48 Å (Đorđević & Karanović 2008), and Ba(AsO 3 OH) with d D-A = 2.46 Å (Đorđević & Karanović 2010). It should be pointed out that Ferraris & Chiari (1970) and Ferraris et al (1972b), respectively, also observed the very short hydrogen-bond distances in weilite (O7...O7 = 2.397 Å) and in švenekite (O5...O5 = 2.436 Å and O8...O8 = 2.444 Å); those hydrogen bonds are symmetrical, rather than asymmetrical, as we observe in vladimirite.…”
Section: Vladimirite (R080001) From Chilementioning
confidence: 99%
“…The S-O bond distance within a sulfate group in the gypsum structure is 1.47 Å [48]. The As-O bond length is roughly 1.69 Å [49], increasing up to 1.79 Å when an H atom is bound to an O in the protonated species.…”
Section: Modeling Resultsmentioning
confidence: 98%
“…For the hydrothermal method, see: Assani et al (2010Assani et al ( , 2011a. For isostructural compounds, see: Zhou et al (2002); Riou et al (1987); Rojo et al (2002); Lightfoot & Cheetham (1988); Kolitsch & Bartu (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…Besides, the investigation of the MO-P 2 O 5 systems (M=divalent cations) has allowed to isolate a new member of the metal phosphates, with a general formula M 7 (PO 4 ) 2 (HPO 4 ) 4 . The present paper aims to develop the hydrothermal synthesis and the structural characterization of the Mg 7 (PO 4 ) 2 (HPO 4 ) 4 which is isostructural with Fe 7 (PO 4 ) 2 (HPO 4 ) 4 (Zhou et al (2002)), Mn 7 (PO 4 ) 2 (HPO 4 ) 4 (Riou et al (1987) and (Rojo et al (2002)), Co 7 (PO 4 ) 2 (HPO 4 ) 4 (Lightfoot & Cheetham, (1988)) and with their homologue arsenate Mg 7 (AsO 4 ) 2 (HAsO 4 ) 4 (Kolitsch & Bartu, (2004)).…”
Section: S1 Commentmentioning
confidence: 99%